If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -6x + 7 = -3 Reorder the terms: 7 + 8x + -6x = -3 Combine like terms: 8x + -6x = 2x 7 + 2x = -3 Solving 7 + 2x = -3 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 2x = -3 + -7 Combine like terms: 7 + -7 = 0 0 + 2x = -3 + -7 2x = -3 + -7 Combine like terms: -3 + -7 = -10 2x = -10 Divide each side by '2'. x = -5 Simplifying x = -5
| x^2-9x-28=0 | | 4x=3x^2-3 | | 8x-21=6x+3 | | 4(3x+6)-6(4x-5)=12x+3(4x-8) | | 57-(4x+4x)+2= | | X^2+8x-25=0 | | x^3-2x^2+49x=98 | | -8m=-1m-14 | | -5(3x-2)= | | x^2(x^2-81)-(x^2-81)=0 | | -5(3*-2)= | | -2n+5+5n=14 | | C=85n+4500 | | 2(3n-2)=(2n+6)+6 | | x(2x-4)+x(6x-3)=(8x+7)(x-2) | | 5*(5-2)+2*6= | | 7-4(x-1)=4x-3 | | x(2x-2)+x(3x-3)=(5x+9)(x-7) | | 7x^2-28x+1=0 | | C-21=47 | | -2X+-8+-8=4 | | 0.8x=400x+400.5 | | 3/2(4x-3)+1/4=1 | | 15=-3(2x-1) | | 4(x-5)=2(x+3) | | -p+3y+10=2p-2 | | 2x-3-8=0 | | 81x=63x+72 | | m+m+2=18 | | -3(1-4x)=2x-3 | | 8x-5-4x=x+5+x | | -4(1-3x)+3x=3x-16 |